A self-directed online resource to enhance coach learning: a 21st-century approach to coach education - Koh, Koon Teck; Santos, Fernando; Newman, Tarkington J. (Frontiers in Sports and Active Living, 2025)
IntroductionPhysical education and sport settings provide dynamic environments conducive to learning values and life skills. However, not every programme that aims to promote healthy youth development has been successful. Such ineffectiveness is often due, in part, to a lack of requisite knowledge and efficacy among coaches. Nonetheless, preliminary research has begun highlighting the potential of online self-directed resources, a contemporary 21st-century approach to coach education and development. The present study explored the development of a coach observation tool (COT) mobile application to support coaches' learning and the participants' perceptions and recommendations of COT for future enhancement.MethodsA total of 34 coach participants from team and individual sports were involved in the present study. Two 60 min lessons were recorded from each participant. The participants were also interviewed individually after the second observation. The lesson plans submitted by the participants were used to link the data generated by the COT mobile application with the percentage of time spent on sports skills, values and life skill development. The COT data were analysed using a paired-sample t-test, while thematic analysis was employed to examine the interview transcripts.Results & discussionFindings indicate that i) key features of the COT are appropriate and practical for coaches; ii) the use of the COT supported self-reflection among coaches, particularly related to facilitative coaching practices and an increased awareness in the designing and delivery of programming. However, additional application features (e.g., incorporating athlete feedback, using Artificial Intelligence for data management) may further enhance the potential to support coach learning effectively. Finally, the theoretical and practical implications for coaches, administrators, and coach educators are discussed.